Study on the heterogeneous material coupling connection characteristics and mechanical strength of Oratosquilla oratoria mantis shrimp saddle. (22nd January 2021) - Liang, Yunhong; Zhang, Hao; Zhao, Qian; Lin, Zhaohua; Zhang, Zhihui; Han, Zhiwu; Ren, Luquan
Abstract: The microstructure, chemical composition and mechanical strength of heterogeneous materials of mantis shrimp ( Oratosquilla oratoria ) saddle were studied. As the key component of the striking system, the saddle comprised two distinct layers including outer layer and inner layer. The outer layer contained blocky microtubules and exhibited compact appearance. The inner layer presented a typical periodic lamellar structure. Due to the change of the thickness of the mineralized outer layer, the organic multilamellar structure became the foundation and enhanced the connection strength (4.55 MPa) at the connect regions between the saddle and merus exoskeleton and membrane, respectively. In the process of fracture, the lamellar structure dispersed the stress effectively by the change of the crack deflection direction and the microfibrils ordered arrangement. The exploration of mantis shrimp saddle region is beneficial to understand the striking system and provided the possibility for the stable connection of heterogeneous materials in engineering fields. The microstructure, heterogeneous material connection characteristics and high mechanical strength of saddle provide bionic models for the preparation of fiber-reinforced resin composites and soft composites.